The Relationship Between Country of Origin, Willingness to Pay More and Purchase Intention: A Study with Turkish Consumers on Apparel Products - Bayraktar Köse, Elçin; Eroğlu, Filiz (Journal of Applied And Theoretical Social Sciences, 2021)
In our rapidly changing world, consumers are being exposed to an increasing amount of product information day by day, while they are trying to make the best choice in the light of this information. This provides a broad scope for marketers involved in marketing practice or research processes to examine the impact of different product information on consumption behavior. The country-of-origin information is seen as a point in consumers mind that has an impact on the quality perception of the relevant products, purchasing preferences and other issues. Consumers may have tendencies to prefer the products of certain countries or have positive perceptions of that country's product. Although it is a crucial issue for both marketing practitioners and academicians, there is still a lack of literature about the impact of consumers’ perceptions towards country of origin of the products on their willingness to pay more and purchase intentions. The aim of the study is to determine the relationship between country of origin (COO), willingness to pay more and purchase intention. Within the scope of the research, the data obtained from 720 consumers were analyzed and then the research model was tested. As a result of the analysis, a significant and positive relationship between the quality perception of the country of origin (COO) and the purchase intention is found. In addition, it was determined that willingness to pay more has an intermediary role in the effect of the quality perception of COO on the purchase intention.